2023
DOI: 10.3390/ijms24031968
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Exosomes in the Diagnose, Development and Therapeutic Resistance of Oral Squamous Cell Carcinoma

Abstract: Oral cancer is one of the most common cancers worldwide, of which more than half of patients are diagnosed at a locally advanced stage with poor prognosis due to recurrence, metastasis and resistant to treatment. Thus, it is imperative to further explore the potential mechanism of development and drug resistance of oral cancer. Exosomes are small endosome-derived lipid nanoparticles that are released by cells. Since the cargoes of exosomes were inherited from their donor cells, the cargo profiles of exosomes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…Previous research has suggested that analyzing the genomic content of exosomes can be a promising approach for studying the mutation landscape associated with cancer, providing a potential avenue for early detection methods [ 5 , 10 , 12 , 17 , 67 , 68 ]. Exosomes not only contain mtDNA but also carry a large amount of nuclear DNA, similar to the gDNA found in cell nuclei, evenly distributed across all chromosomes; this further reveals their significance and potential influence in various biological processes [ 24 , 31 , 69 ].…”
Section: Research Progress On the Application Of Exodna In Lbmentioning
confidence: 99%
“…Previous research has suggested that analyzing the genomic content of exosomes can be a promising approach for studying the mutation landscape associated with cancer, providing a potential avenue for early detection methods [ 5 , 10 , 12 , 17 , 67 , 68 ]. Exosomes not only contain mtDNA but also carry a large amount of nuclear DNA, similar to the gDNA found in cell nuclei, evenly distributed across all chromosomes; this further reveals their significance and potential influence in various biological processes [ 24 , 31 , 69 ].…”
Section: Research Progress On the Application Of Exodna In Lbmentioning
confidence: 99%
“…Despite the advances in different treatment modalities, the overall survival rate of OSCC 5 -year is less than 50% which is not improved signi cantly during the past decades due to delayed diagnosis (9). Survival rate can be increased to 80% if OSCC are diagnosed in the early stages (10).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are nanosized extracellular vehicles having origins in the re-cycling of intracellular vesicles. They have demonstrated that they exert a key role in intercellular communication in both physiological and pathological scenarios [12][13][14][15]. Exosomes are the natural cargo vesicles for proteins, DNAs, RNAs, lipids, and metabolites that are essential in a myriad of physiological and pathological functions [16,17].…”
Section: Introductionmentioning
confidence: 99%